2018
DOI: 10.5964/ijpr.v12i1.284
|View full text |Cite
|
Sign up to set email alerts
|

Subjective well-being and personal relationships in childhood: Comparison of Brazilian and Spanish children

Abstract: This study aims to compare personal relationships satisfaction and subjective well-being of Brazilian and Spanish children and to verify if personal relationships are associated with subjective well-being for the sample. Participants are 6,747 children aged from 11 to 14 years old (M = 12.07, DP = 0.731), 1,020 being Brazilian and the others Spanish. From the total sample 50.7% were girls. Results pointed that the items of personal relationships are grouped into three components related to family, school and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 54 publications
1
14
1
1
Order By: Relevance
“…Likewise, there were higher levels of satisfaction with family life in the three family members belonging to the balanced families. This latter finding is in line with studies that have stressed the importance of family relationships and satisfaction with family life for well-being in adults and adolescents (Castellá, Casas, Ramos, Bedin, & González, 2018;Lawler, Newland, Giger, Roh, & Brockevelt, 2017;Schnettler, Miranda-Zapata, et al, 2018). Therefore, it can be suggested that family life satisfaction in all family members must be promoted to achieve balanced families in terms of life satisfaction.…”
Section: Discussionsupporting
confidence: 87%
“…Likewise, there were higher levels of satisfaction with family life in the three family members belonging to the balanced families. This latter finding is in line with studies that have stressed the importance of family relationships and satisfaction with family life for well-being in adults and adolescents (Castellá, Casas, Ramos, Bedin, & González, 2018;Lawler, Newland, Giger, Roh, & Brockevelt, 2017;Schnettler, Miranda-Zapata, et al, 2018). Therefore, it can be suggested that family life satisfaction in all family members must be promoted to achieve balanced families in terms of life satisfaction.…”
Section: Discussionsupporting
confidence: 87%
“…Los resultados se añaden a la evidencia que indica que se debe apostar por modelos explicativos de la satisfacción con la vida como los propuestos en otros estudios (Moreno y Vera, 2011), los cuales integran tanto variables de carácter intraindividual como factores ambientales y sociales. Este tipo de modelos son los que más se ajustan y explican la realidad de los adolescentes y su interacción con el contexto que los rodea (Crous et al, 2018;Sarriera et al, 2018;Casas, 2011).…”
Section: Discussionunclassified
“…This interest has provided the impetus for a range of empirical studies exploring macro and micro-level associations and correlates of children's SWB. Within this rapidly expanding body of empirical evidence, children's social relationships have increasingly demonstrated significant relations with their SWB (see Goswami, 2012;Gray et al, 2013;Haanpää & af Ursin, 2018;Haanpää et al, 2019;Holder & Coleman, 2009;Lau & Bradshaw, 2018;Lee & Yoo, 2015;McAuley et al, 2012;Sarriera et al, 2018;Savahl et al, 2020). Within the extant literature on positive psychology, social relationships are strongly associated with positive well-being (Holder & Coleman, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Families are an integral part of society and provide the first context within which children learn to live life, serving as their primary source of social capital (see Sarriera et al, 2018). Within this context, children learn basic social skills which are further reflected in their interactions with society.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation